Comparative energy and environmental analysis of Jatropha bioelectricity versus biodiesel production in remote areas. (1st April 2015) - Portugal-Pereira, Joana; Nakatani, Jun; Kurisu, Kiyo H.; Hanaki, Keisuke
Abstract: This study presents a comparative analysis between Jatropha seed production systems to generate bioelectricity versus production of biodiesel under current and optimised conditions. An LCA (life cycle assessment) has been developed, comprising both upstream and downstream processes, encompassing the farming, collection, fuel processing and usage phases. The following energy and environmental indicators were assessed: fossil depletion, GWP (global warming potential), TAP (terrestrial acidification potential ), and PMF (particulate matter formation). The rural electrification based on the JCO ( Jatropha crude oil) system is more environmentally friendly compared to generation of biodiesel, in terms of TAP and PMF indicators. Under current practices, two out of the four evaluated indicators score positive benefits, when compared to the generation of marginal diesel-based electricity. The optimisation of the expelling pressing process and the power generation engine could bring further improvements in terms of fossil depletion, GWP and PMF indicators. The biodiesel route, on the other hand, presents a limited local environmental performance, showing only gains in terms of fossil depletion and GWP. Highlights: Comparison of Jatropha life cycle to generate electricity and vehicular biodiesel. Well to Wheel LCA evaluates energy, local and global environmental indicators. Electrification based on the Jatropha crude oil is more competitive than biodiesel. Optimised expelling and power generation engine bring energy and environmental savings.